Embolic Stroke of Undetermined Source: Towards a More Tailored Approach - Kamel, Hooman (JAMA Neurol, 2019)
IMPORTANCE: One-third of ischemic strokes have no identifiable cause after standard evaluation. In 2014, Hart et al termed these “embolic strokes of undetermined source” (ESUS) and argued that this entity would respond to anticoagulation. Two recent trials did not uphold this hypothesis, leading to questions about the ESUS concept. OBSERVATIONS: We propose that ESUS remains a useful concept, the clinical impact of which can be enhanced by considering two subsets defined by their likelihood of responding to anticoagulation. Recent studies indicate that some ESUS cases result from subclinical atrial fibrillation, atrial cardiopathy, unrecognized myocardial infarction, patent foramen ovale, or cancer, while other cases result from nonstenosing large-artery atherosclerosis, aortic atherosclerosis, or non-atherosclerotic vasculopathies. Evidence suggests that anticoagulation will prove superior to antiplatelet therapy for the former group of etiologies but not the latter, suggesting the need for personalized therapy. CONCLUSIONS AND RELEVANCE: Although the ESUS concept as currently constructed cannot guide treatment, efforts to better understand ESUS and develop therapies tailored to specific mechanisms are likely to help reduce the burden of stroke.